RELATIONSHIPS BETWEEN INITIAL PROBING DEPTH AND CHANGES IN THE CLINICAL PARAMETERS FOLLOWING NON-SURGICAL PERIODONTAL TREATMENT IN CHRONIC PERIODONTITIS - KURU, LEYLA (ISTANBUL UNIV PRESS, ISTANBUL UNIV RECTORATE, 2017)
Purpose: The aim of this study was to evaluate the relationship between initial probing depth (IPD) and changes in clinical parameters following non-surgical periodontal treatment (NPT) in chronic periodontitis patients. Subjects and Methods: A total of 1672 periodontal pockets having 3mm <= IPD <= 9mm of depth in 15 chronic periodontitis patients were included. NPT consisting of oral hygiene instructions, scaling and root planing was applied in two sessions. Probing depth (PD), clinical attachment level, gingival recessions (GR) were measured before and eight weeks after treatment. Pocket sites were grouped according to their IPD and root number as single-or multi-rooted teeth. Results: Other than the sites having 3 mm IPD, PD reduction and GR increase were significant in all groups (p<0.001). Attachment gains (AG) were significant in all single-rooted teeth (p<0.001) again except those having IPD=3mm. However, AG was significant in multi-rooted teeth having only 7mm <= IPD <= 9mm (p<0.05). Positive correlations were observed between IPD and PD reduction, GR increase and AG in single-rooted teeth (p<0.001). Furthermore, positive correlations were found between IPD and PD reduction and GR increase in multi-rooted teeth (p<0.001), but there was no correlation between IPD and AG. Conclusion: NPT may lead to positive association between IPD and PD reduction as well as GR increase, which is independent from tooth root anatomy.
Keywords: Chronic periodontitis; dental scaling; periodontal pocket; root planning; periodontology; SUBGINGIVAL MICROBIAL-FLORA; THERAPY; DEBRIDEMENT; ATTACHMENT; EFFICACY; DISEASES; TISSUES; TRIAL